2018
DOI: 10.3389/fmars.2018.00472
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and High Transport of Particles and Solutes by Benthos in Coastal Eutrophic Sediments of the Pomeranian Bay

Abstract: We present results on bioirrigation and reworking of sediments by benthic macrofauna in sediments of the Pomeranian Bay (southern Baltic Sea), that were obtained ∼22 years ago. The investigation took place at four stations ranging from 9 to 19 m water depth, which we observed between 1993 and 1995 over the course of 30 months. In order to assess exchange of solutes across and particles from the sedimentwater interface with the underlying sediments, we used bromide as ex situ tracer for bioirrigation and chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Published global estimates, such as those based on relationships between bottom water oxygen and nitrogen loss [ 46 ], fluxes of phosphorus [ 47 ] and biogenic silica [ 48 ] appeared to be too coarse in spatial resolution when compared to our investigation. Apart from negligible sampling size, the weak relationship between estimated BIPc values in this study and irrigation volumes from Powilleit and Forster [ 43 ] (based on a handful of stations) could be associated with the poor performance of the index, or also with experimental artefacts arising during the measurements. The differences in association for different sediment layers indicated that correspondence between the Br transport and fauna is blurred close the sediment–water interface where, in addition to bioirrigation, molecular diffusion drives tracer fluxes most.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Published global estimates, such as those based on relationships between bottom water oxygen and nitrogen loss [ 46 ], fluxes of phosphorus [ 47 ] and biogenic silica [ 48 ] appeared to be too coarse in spatial resolution when compared to our investigation. Apart from negligible sampling size, the weak relationship between estimated BIPc values in this study and irrigation volumes from Powilleit and Forster [ 43 ] (based on a handful of stations) could be associated with the poor performance of the index, or also with experimental artefacts arising during the measurements. The differences in association for different sediment layers indicated that correspondence between the Br transport and fauna is blurred close the sediment–water interface where, in addition to bioirrigation, molecular diffusion drives tracer fluxes most.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, the spatial pattern of the tracer in pore waters also showed a positive association with BIPc values. A correlation of index with bioirrigation constants calculated for various depth intervals reported in Powilleit and Forster [ 43 ] was not significant, but this is not surprising due to the very low sample size. The strength of linear association was higher for deeper sediment depth intervals.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Accumulation of organic matter and intense sediment reworking (i.e. physical mixing) can have a substantial influence on sediment biogeochemistry (Welsh 2003, McKindsey et al 2011, Kristensen et al 2012, Wendelboe et al 2013, Koo & Seo 2017, Powilleit & Forster 2018.…”
Section: Open Pen Access Ccessmentioning
confidence: 99%